Reviews on the socio-economic indicators for spatial urban scale - Ibrahim, Illyani; Abu Samah, Azizan; Asmawi, M. Zainora (MIP, 2017)
In recent decades, socio-economic variables have been widely used to investigate regional scale particularly in climate change studies. This paper aims to review appropriate socio-economic indicators for studies related to environment and climate at the level of spatial urban scale. It has been a challenge to select appropriate indicators because the interrelationship between human interference and the environment has proved difficult to be understood. The method used for the review is content analysis. The finding proposes the future research to choose suitable socio-economic indicators by referring to the scale of study and the spatial coverage of the topic. This article also provides a socio-economic framework to ensure that the appropriate of urban scale is the key aspect for selection of indicators in environmental and climate related studies.